2008
DOI: 10.4238/vol7-1gmr418
|View full text |Cite
|
Sign up to set email alerts
|

Effects of polymorphisms of LHR and FSHR genes on sexual precocity in a Bos taurus x Bos indicusbeef composite population

Abstract: ABSTRACT. The purpose of the present research was to investigate the effects of polymorphisms of luteinizing hormone receptor (LHR) and follicle-stimulating hormone receptor (FSHR) genes, evaluated by polymerase chain reaction-restriction fragment length polymorphism in EuropeanZebu composite beef heifers from six different breed compositions. The polymorphism site analysis from digestion with HhaI and AluI restriction endonucleases allowed the genotype identification for LHR (TT, CT and CC) and FSHR (GG, CG a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 10 publications
(6 reference statements)
2
21
0
3
Order By: Relevance
“…This result is consistent with that of a previous study (Shirasuna et al, 2011), which examined a Holstein population, but the frequency was different from the study of Marson et al (2008), who examined crossbred dairy cattle in their study.…”
Section: Alleles Genotypes and Composite Genotype Frequencysupporting
confidence: 89%
See 2 more Smart Citations
“…This result is consistent with that of a previous study (Shirasuna et al, 2011), which examined a Holstein population, but the frequency was different from the study of Marson et al (2008), who examined crossbred dairy cattle in their study.…”
Section: Alleles Genotypes and Composite Genotype Frequencysupporting
confidence: 89%
“…The method described by Kuehn et al (2007) was used to study polymorphisms of the DGAT1 gene. PCR-RFLP and the methods described by Marson et al (2008) and Rachagani et al (2006) were used to genotype the LHR, beta-LGB, and GH genes, respectively.…”
Section: Genotypingmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have indicated that the FSHR gene plays important roles in human hormone secretion, menstrual cycle, ovarian development, and other reproductive processes (Sairam and Subbarayan, 1997;Marson et al, 2008;Achrekar et al, 2009a;Balkan et al, 2010;Rendina et al, 2010;Dolfin et al, 2011;Kang et al, 2012;Grigorova et al, 2008Grigorova et al, , 2013. However, the relationship between FSHR polymorphisms and reproductive traits in swine has not been thoroughly examined.…”
Section: Effect Of Fshr Polymorphisms On Animal Reproductive Traitsmentioning
confidence: 99%
“…A study by Rahal et al (2000) detected 2 SNPs (C1506T and T1593C) in exon 10 of the bovine FSHR gene. Marson et al (2008) found no correlation between FSHR gene polymorphisms and precocious puberty in heifers, while a study by Sairam and Subbarayan (1997) identified a correlation between FSHR gene polymorphisms and the secretion of reproductive hormones in seasonally breeding mammals. Finally, studies by Jiang et al (2002) revealed that polymorphisms in exon 10 of the porcine FSHR gene significantly affected the number of offspring.…”
Section: Introductionmentioning
confidence: 95%